EU-Brazil proposal on farm support: strengthening agricultural reforms or undermining them? - Sachin Kumar Sharma; Abhijit Das (Agricultural Economics Research Review, 2023)
Developing countries have been demanding substantial reduction in trade distorting domestic support to agriculture given by the developed countries. On the other hand, under the existing rules of the Agreement on Agriculture (AoA) many developing countries lack policy space to implement price support measures to augment income of the farmers. Of late, some member countries of WTO namely, Brazil, European Union, Colombia, Peru and Uruguay circulated a proposal on Overall Trade Distorting Support (OTDS) seeking a cap on trade distorting spending. This study critically examines the implications of EU-Brazil proposal regarding OTDS on the flexibility for the member countries to provide domestic support to agriculture. The results show that EU-Brazil proposal is likely to result in a steep reduction in policy space for the developing countries, which is already limited and insufficient for implementing agricultural policies. Concurrently, USA and EU will undertake negligible or no reductions in trade distorting support to agriculture and preserve their existing flexibilities in future as well. Contrary to Doha Declaration, this proposal is providing special and differential treatment to EU and USA.